Efektivitas Pijat Oksitosin terhadap Produksi Asi pada Ibu Nifas Hari ke 1-3 - Isne Susanti; Nesya Meylita Salva Putri; Eka Oktavia (Jurnal Kesehatan Amanah, 2025)
Breast milk is a natural food for newborns that can influence their growth and development. Breast milk is given without any additives to babies from zero to six months of age. The WHO recommends exclusive breastfeeding from zero to six months of age, but implementation remains uneven in some regions. According to the Indonesian Ministry of Health, national exclusive breastfeeding coverage in 2022 was 67.96%, below the RPJMN target of 70%. In the Special Region of Yogyakarta (DIY) Province, the figure reached 76.8% in 2022, with Yogyakarta City having the lowest achievement compared to other regencies. This results in suboptimal breast milk production. To increase breast milk production in mothers, oxytocin massage techniques can be used.. This method was chosen because it is non-pharmacological, easy to do and proven to be able to stimulate the hormone oxytocin. easy to do and proven to be able to stimulate the hormone oxytocin. This study aims to determine the effectiveness of oxytocin massage in influencing breast milk production in postpartum mothers at Nur Hidayah Hospital. Quantitative research method with quasi-experimental design, Respondents were 30 people obtained through accidental sampling. Data collection used a directed observation sheet and measuring cup (cc). The results of the Independent Sample T Test analysis showed a significance value of 0.001 (p <0.05) meaning that there is effectiveness of oxytocin massage on breast milk production in postpartum mothers on days 1-3. The conclusion of the study is that there is effectiveness of oxytocin massage on breast milk production in postpartum mothers on days 1-3.